2019
DOI: 10.1007/s11187-019-00285-z
|View full text |Cite
|
Sign up to set email alerts
|

SME access to market-based finance across Eurozone countries

Abstract: This paper provides an in-depth analysis of SME access to capital markets across Eurozone countries. First, we determine which factors -at firm and country level -influence the likelihood of SME access to market-based finance. Second, we construct an index of market suitability to indicate the percentage of firms potentially fit for market-based finance. Our results suggest that while several Eurozone countries have realised SMEs' 'potential' for capital market financing, a large number of firms fit for market… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…For this purpose, we compared the first third of the survey responses with the last third of the survey responses and found no significant differences between these groups (Armstrong & Overton, 1977). We can confirm the representativeness of our sample by showing that comparable distributions in terms of industries, company size, company age, and the age of the respondent are present in validated peer reviewed articles about SMEs in Germany (Bongini et al, 2021;Dehlen et al, 2014;Werner et al, 2018). Furthermore, we assured all respondents absolute anonymity and scientific integrity to obtain the most honest responses possible and to prevent a possible social desirability bias (Podsakoff et al, 2003).…”
Section: Datasetsupporting
confidence: 59%
“…For this purpose, we compared the first third of the survey responses with the last third of the survey responses and found no significant differences between these groups (Armstrong & Overton, 1977). We can confirm the representativeness of our sample by showing that comparable distributions in terms of industries, company size, company age, and the age of the respondent are present in validated peer reviewed articles about SMEs in Germany (Bongini et al, 2021;Dehlen et al, 2014;Werner et al, 2018). Furthermore, we assured all respondents absolute anonymity and scientific integrity to obtain the most honest responses possible and to prevent a possible social desirability bias (Podsakoff et al, 2003).…”
Section: Datasetsupporting
confidence: 59%
“…Nivorozhkin, 2004;Delcoure, 2007;Kędzior, 2012;Koralun-Bereźnicka, 2013). The macroeconomic and institutional factors were confirmed to influence the likelihood of SMEs accessing market-based finance (including issue of new shares) in the recent study by Bongini et al (2019). However, some studies provided contrary results and suggested that firm-specific factors (such as: age, size, profitability, asset structure, growth rate, ownership structure) are more important (e.g.…”
Section: Methodsmentioning
confidence: 88%
“…The SAFE survey is published annually (since 2013) and covers all EU member states. The investigation considers the results of five consecutive annual SAFE reports, for 2014-2018 time span (2013 was excluded, as the structure of survey in 2013 was slightly different in comparison to Bongini et al (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, innovative firms have higher probabilities in demanding financial instruments but lower probabilities in accessing to them. Bongini et al (2019) analyse which are the characteristics of the firms and the country that affect the probability that firms could access to the capital market. These authors construct an indicator called index of market suitability and find that the macroeconomic conditions of the countries affect the suitability to access the capital market of SMEs.…”
Section: Smes Profile and Financing Access Under The Lens Of Safementioning
confidence: 99%